Piperine-Hydroxy acid-Cyclodextrin Inclusion Complexes; Physicochemical, Computational, and Proton Nuclear Magnetic Resonance Spectroscopy Studies: PART I - Jadhav, Priyanka (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: In an attempt to improve the physicochemical properties of piperine (PIP), its inclusion complexes were prepared with Î²-cyclodextrin (Î²CD) and hydroxypropyl-Î²-cyclodextrin (HPÎ²CD) in presence and/or absence of hydroxy acids by lyophilization technique. Materials and Methods: Primarily, the stoichiometry of the complex formation and thermodynamic parameters was accessed by phase solubility study described by Higuchi and Conners method. The molecular modeling studies were performed to elucidate the stability, possible interactions, and geometry of PIP inside the Î²CD cavity. The prepared lyophilized inclusion complexes were characterized by proton nuclear magnetic resonance spectroscopy (1H NMR) and Two-dimensional Nuclear Overhauser Effect spectroscopy (2D 1H NMR), Fourier transformation-infrared spectroscopic (FTIR), scanning electron microscopic (SEM), Log P, and dissolution studies. Results: The phase solubility data revealed the formation of 1:1 stoichiometry with AL type of solubility curve at 25Â°C. Thermodynamic studies indicated that the inclusion process was spontaneous. The molecular modeling studies were depicted the insertion of piperidine ring inside Î²CD cavity. As complementary evidence, 1H NMR and 2D 1H NMR studies predicted that whether in presence or absence of hydroxy acids, CD is able to accommodate the piperidine ring. FTIR analysis revealed scattering peaks assigned for PIP were smoothened in all lyophilized inclusion complexes. SEM images indicated modifications in morphology of PIP particles in its lyophilized complexes. Dissolution studies revealed significant improvement in dissolution efficiencies of PIP in all prepared inclusion complexes. Conclusion: The effectiveness of ternary hydroxy acids was found to be appreciating toward improvement in aqueous solubility and dissolution properties of PIP.